Unquestioned Gender Lens in Contemporary Indonesian Shariâah-Ordinances (Perda Syariah) - Candraningrum, Dewi (Al-Jamiah: Journal of Islamic Studies, 2007)
Indonesian muslim participation in the democratic arena is now contested with the arrival of the decentralization process in 423 districts since 1992. The most notable movement is the quest for Islamic identity in the rejuvenation of Shari âah Ordinances which is interpreted symbolically and transcripturally. These ordinances have unrecognized the importance of gender lens in its practice. Until the end of 2007 no less than 63 districts have ratified Perda Syariâah. In general, these ordinances designed to govern three aspects of public life, namely (1) to eradicate social crimes especially prostitutions and gambling; (2) to enforce ritual observances among Muslims such as reading the Qurâan, Friday congregations and fasting during Ramadan; and (3) to govern the way people dress up in public sphere especially the head-veiling for women. Although Islam is the religion of the majority there are also non-muslim among Indonesian and institutionally Indonesia is not an Islamic state, therefore the ratification of Perda Syariâah betrayed national consensus agreed upon by the founding fathers of the republic.